2019
DOI: 10.2478/aiht-2019-70-3372
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of parabens and plastic nanoparticles on proliferation of human breast cancer cells

Abstract: Many personal care products on the market contain endocrine disrupting chemicals, including parabens. Parabens are well known chemical additives used as preservatives. They have been found in mammary glands and breast cancer tissues. At the same time, the general public is increasingly exposed to plastic micro- and nanoparticles generated during plastic production and waste disposal. Exposure to chemical cocktails is a realistic scenario of high public health interest, in which many types of compounds such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Currently PBs are classified as endocrine disruptors, which have genotoxic and cytotoxic effects 15 , 16 and affect many internal organs and systems, mainly including the reproductive, immune and endocrine systems 17 20 . Some studies have also reported correlations between PBs and obesity, disorders in the nervous system developmental disorders and neoplastic processes 11 , 21 23 . Due to adverse effects of PBs, the legislation of many countries has introduced the limitation of these substances.…”
Section: Introductionmentioning
confidence: 99%
“…Currently PBs are classified as endocrine disruptors, which have genotoxic and cytotoxic effects 15 , 16 and affect many internal organs and systems, mainly including the reproductive, immune and endocrine systems 17 20 . Some studies have also reported correlations between PBs and obesity, disorders in the nervous system developmental disorders and neoplastic processes 11 , 21 23 . Due to adverse effects of PBs, the legislation of many countries has introduced the limitation of these substances.…”
Section: Introductionmentioning
confidence: 99%
“…Still because of their small size, nanoparticles can translocate and reach the systemic circulation to be potentially distributed to other organs. This explains why some studies investigated the damages to the cardio-vascular system (Asweto et al, 2017;Feng et al, 2018Feng et al, , 2017 and to other organs (Cotena et al, 2021;Courter et al, 2007;Deville et al, 2016;Ku et al, 2017;Lai et al, 2020;Roje et al, 2019;Schirinzi et al, 2017;Teng et al, 2020;Xia et al, 2011). Among the different organs, the digestive system is quite well studied (Ahamed et al, 2020a(Ahamed et al, , 2019bCao et al, 2021Cao et al, , 2019Dussert et al, 2020;Shi et al, 2010;Zheng et al, 2012).…”
Section: A Literature Review On the Joint Toxicity Of Nanoparticles And Co-contaminantsmentioning
confidence: 99%
“…In Table 2, the category other/ various includes studies on the nervous system (Ku et al, 2017;Schirinzi et al, 2017), immune system (Deville et al, 2016), kidney cells (Xia et al, 2011), breast cells (Roje et al, 2019), on carcinogenesis (Courter et al, 2007), reproductive organs (Cotena et al, 2021), fetus (Teng et al, 2020) or deal with global effects, affecting several organs (Courter et al, 2007;Lai et al, 2020;Teng et al, 2020).…”
Section: A Literature Review On the Joint Toxicity Of Nanoparticles And Co-contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of parabens, specifically in human breast cancer tissue, moreover implied their potential to drive the sustained proliferation of breast epithelial cells that possess estrogen receptors (ER), specifically the estrogen receptor alpha (ERα). [ 5–8 ]…”
Section: Introductionmentioning
confidence: 99%